The Crocus sativus Compounds trans-Crocin 4 and trans-Crocetin Modulate the Amyloidogenic Pathway and Tau Misprocessing in Alzheimer Disease Neuronal Cell Culture Models - Chalatsa, Ioanna; Arvanitis, Demetrios A.; Koulakiotis, Nikolaos Stavros; Giagini, Athina; Skaltsounis, Alexios Leandros; Papadopoulou-Daifoti, Zeta; Tsarbopoulos, Anthony; Sanoudou, Despina (Frontiers in Neuroscience, 2019)
Crocus sativus L. natural compounds have been extensively used in traditional medicine for thousands of years. Recent research evidence is now emerging in support of its therapeutic potential for different pathologies including neurodegenerative diseases. Herein, the Crocus sativus L. natural compounds trans-crocin 4 and trans-crocetin were selected for in depth molecular characterization of their potentially protective effects against Alzheimer’s Disease (AD), utilizing two AD neuronal cell culture models (SH-SY5Y overexpressing APP and PC12 expressing hyperphosphorylated tau). Biologically relevant concentrations, ranging from 0.1 μM to 1 mM, applied for 24h or 72h, were well tolerated by differentiated wild type SH-SY5Y and PC12 cells. When tested on neuronally differentiated SH-SY5Y-APP both trans-crocin 4 and trans-crocetin had significant effects against amyloidogenic pathways. Trans-crocin 4 significantly decreased of β-secretase, a key enzyme of the amyloidogenic pathway, and APP-C99, while it decreased γ-secretases that generate toxic beta-amyloid peptides. Similarly, trans-crocetin treatment led to a reduction in β- and γ-secretases, as well as to accumulation of cellular ΑβPP. When tested on the neuronally differentiated PC12-htau cells, both compounds proved effective in suppressing the active forms of GSK3β and ERK1/2 kinases, as well as significantly reducing total tau and tau phosphorylation. Collectively, our data demonstrate a potent effect of trans-crocin 4 and trans-crocetin in suppressing key molecular pathways of AD pathogenesis, rendering them a promising tool in the prevention and potentially the treatment of AD.